Saint Menas and His Miracles in the Ethiopian Tradition - Rafał Zarzeczny (Vox Patrum)
The fame of St Menas, the Egyptian martyr, spread far beyond Egypt, extending into historical Ethiopia. This widespread reverence stems from the longstanding unity between the Churches of Alexandria and Ethiopia, alongside the significant translation of Copto-Arabic texts into the classical Ethiopic language. By the fourteenth century, The Life and Martyrdom of St Menas was translated into Ge‘ez and became part of the Gadla Samāʽetāt collection of accounts on other prominent saints and martyrs. A concise version of St Menas’s acts appears in the hagiographical compilation for liturgical use, the Synaxarium. Ethiopia commemorates St Menas on Ḫedār 15 and the construction of his shrine at Maryut on Sanē 15. The latter occasion entails reading aloud a comprehensive collection of nineteen miracles, also translated from Arabic. The image of a saint who defends devout pilgrims like a knight, protects his sanctuary, heals the sick, liberates the possessed, punishes sins, repairs damage, and bestows blessings upon worshippers, evoked awe, reverence, and piety, especially in the Horn of Africa. Additional texts, including hymns and antiphons, further underscore the cult’s vitality. St Menas’s canonical depiction on horseback aligns with the broader tradition of equestrian saints, a frequent motif in Ethiopian iconography.